ATRIAL FLUTTER IN HYPERTHYROIDISM: ACHIEVING EARLY RHYTHM CONTROL - Zulkufi, M. Razi; Subbarao, H.K.R; MS, Mohd Syafiq; S, Salbiah; Rus, Rafizi Mohamed (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION Atrial arrhythmia is a common manifestation of cardiac complications of hyperthyroidism. However, most literature focus on the incidence and management of atrial fibrillation rather than atrial flutter. It also suggests postponement of cardioversion until the fourth month of maintaining a euthyroid state, as more than half of cases revert spontaneously to sinus rhythm and atrial fibrillation may recur with thyrotoxicosis. Here we present a case of atrial flutter with early rhythm control with electrical cardioversion without subsequent recurrence. CASE A 29-year-old male presented with a two-day history of fever and recurrent episodes of palpitations. Upon arrival, findings showed BP 110/70, temperature 38°C, and typical counterclockwise atrial flutter with variable block and HR 130 bpm on ECG. Results revealed low TSH (<0.01 mIU/L) and elevated FT4 (90 pmol/L). He was treated as Graves’ thyrotoxicosis precipitated by viral fever. Treatment included carbimazole 30 mg OD, rate control with propanolol 40 mg TDS and supportive care. Echocardiogram showed EF 44% with dilated RA, RV and LA. In view of evidence of cardiomyopathy, transoesophageal echocardiogram and elective cardioversion was performed a week after discharge. Rhythm was successfully cardioverted back to sinus rhythm. He remains in sinus rhythm with improvement in cardiac function four weeks after cardioversion. CONCLUSION In general, the management of atrial flutter is slightly different from atrial fibrillation, as the former may be treated with immediate rhythm control using electrical cardioversion. Despite the thyrotoxic state, earlier rhythm control is better for cases of atrial flutter in order to prevent development or worsening of thyrotoxic cardiomyopathy.